A network traffic prediction model based on recurrent wavelet neural network - Zhang, Kun; Chai, Yinping; Fu, Xing-an (2012 2nd International Conference on Computer Science and Network Technology, 2012)
The network traffic prediction model is the foundation of network performance analysis and designing. The traditional traffic models have the weakness of low-level efficiency. The recurrent wavelet neural network(RWNN) based on E Iman network was proposed in the paper, and the dynamic gradient descent algorithm of RWNN was given, and could be used in the network traffic prediction. Experimental results show that the network traffic prediction model based on RWNN is feasible and effective.